Methane emission and nutritive evaluation of green, black, oolong, and white tea leaves (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wahyuni S, Sudarman A, Sofyan A, Permata D, Darma ING, Ramdani D, Hidayatik N, Jayanegara A. 2025. Methane emission and nutritive evaluation of green, black, oolong, and white tea leaves. Biodiversitas 26: 3423-3433. This study aimed to evaluate the impact of non-fermented and fermented leaves of green tea, black tea, oolong tea, and white tea on nutritive value, methane emission, and in vitro ruminal fermentation characteristics. Each type of tea leaves was prepared in both fresh (non-fermented) and fermented forms. Fermented tea leaves were treated with water in a 1:2 ratio. Each treatment was prepared in five replicates and incubated for 30 days. A completely randomized factorial design was applied, with tea type as the primary factor and fermentation status (non-fermented and fermented) as the secondary factor. Results revealed that the highest crude protein content was found in white tea (29.41%), followed by green tea (17.87%). There was a significant effect (p
Keywords: Chemical composition, fermentation, in vitro rumen, methane emission, tea leaves